Telaah Sistem Evaluasi Kurikulum 13 Di SDN 16 Tanjung Batu - Atina Rahmatia; Erina Erina; Erwin Ammar Fadilah; Septi Anggraini; Dwi Noviani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The 2013 curriculum has been implemented at various levels of education in Indonesia, including elementary schools (SD). This research aims to examine the 2013 Curriculum evaluation system at SDN 16 Tanjung Batu, with a focus on the evaluation process, evaluation instruments, and implementation of evaluation results. The research method used is literature study and secondary data analysis. The purpose of this 2013 curriculum research is to find solutions to all existing problems in order to achieve good, quality education and its implications for the progress of a nation and state. The research results show that the 2013 Curriculum evaluation system at SDN 16 Tanjung Batu still experiences several obstacles, such as lack of clarity in the evaluation process, lack of valid and reliable evaluation instruments, and minimal implementation of evaluation results in improving learning. This research also identified several recommendations for improving the 2013 Curriculum evaluation system at SDN 16 Tanjung Batu, including developing evaluation instruments that are appropriate to learning objectives, training for educators in conducting effective evaluations, and using evaluation results as a basis for designing curriculum improvements. Apart from training for educators, educators must also undergo coaching and workshops regarding these programs. So that the program can run well if it is prepared carefully, with the government socializing it so that there is continuity by taking level interests into account. It is hoped that the findings from this research can provide input for schools, teachers and related stakeholders in improving the effectiveness of the 2013 Curriculum evaluation system at SDN 16 Tanjung Batu, so that it can support better achievement of learning goals.